2006
DOI: 10.1007/s10552-005-0389-0
|View full text |Cite
|
Sign up to set email alerts
|

A Pooled Analysis of Bladder Cancer Case–Control Studies Evaluating Smoking in Men and Women

Abstract: These results do not support the hypothesis that women have a higher relative risk of smoking-related bladder cancer than men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 39 publications
1
22
1
1
Order By: Relevance
“…25,26 Previous studies have found PARs of 50-65% in men and 20-30% in women but were conducted in populations where the prevalence of smoking in women was considerably lower than in men. [27][28][29][30][31] Renal impairment was also an important issue in the timely management of the NMIBC population in this part of the world as suggested by the presented data. Up to 40% of patients with bladder cancer have renal impairment, defined as a creatinine clearance ≤60 ml/min, as calculated by the Cockroft-Gault formula.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Previous studies have found PARs of 50-65% in men and 20-30% in women but were conducted in populations where the prevalence of smoking in women was considerably lower than in men. [27][28][29][30][31] Renal impairment was also an important issue in the timely management of the NMIBC population in this part of the world as suggested by the presented data. Up to 40% of patients with bladder cancer have renal impairment, defined as a creatinine clearance ≤60 ml/min, as calculated by the Cockroft-Gault formula.…”
Section: Discussionmentioning
confidence: 99%
“…19 Epidemiologically, postmenopausal women have a higher risk of development and progression of UBC than premenopausal women. 20 Also, smoking is one of the major risks of urinary tract cancer and considered to increase the cancer risk by approximately threefold, 21,22 and the percentage of smokers is much higher in males than in females in Japan (36.8 versus 9.1%, as of 2008 in the National Survey by the Ministry of Health, Labour and Welfare of Japan). If such environmental and life style-related factors contribute to the predisposition of bladder cancer together with POLG2, this may explain the observed effect of POLG2 with UBC invasiveness in males only.…”
Section: Discussionmentioning
confidence: 99%
“…Additional cases from the NIC members enhanced stability of the background rates of urothelial carcinoma incidence. For those who smoked, cross-tabulation included timevarying levels of intensity (cut points at: 3,8,13,18,23,33,43. cigarettes/day), duration of smoking, and years since quitting (cut points at: 5, 10, 20, 30. years).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Numerous epidemiological studies have reported associations between ionizing radiation (IR) exposure and bladder cancer (1)(2)(3)(4)(5)(6), while others have reported associations between lifestyle factors and bladder cancer, particularly smoking (7)(8)(9)(10)(11). In the most recent cancer incidence report on the Life Span Study (LSS) of A-bomb survivors, the urinary bladder had the highest excess relative risk (ERR) per unit dose of radiation of any of the solid cancers other than the female breast (ERR/gray weighted bladder dose ¼ 1.23) (1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation